Traditional Tibetan Medicine Twenty-Five Wei’er Tea Pills Ameliorate Rheumatoid Arthritis Based on Chemical Crosstalk Between Gut Microbiota and the Host - Li, Zixuan; Nie, Lijuan; Li, Yong; Yang, Lu; Jin, Lulu; Du, Baozhong; Yang, Juan; Zhang, Xulin; Cui, Huantian; Luobu, Ouzhu (Frontiers in Pharmacology, 2022)
Twenty-Five Wei’er Tea Pills (TFP), a traditional Tibetan medicine, has shown to have a promising therapeutic effect in patients with Rheumatoid arthritis (RA), as well as being safe. Nonetheless, there have been limited pharmacological studies that have explored this therapeutic option. As gut microbiota has been proven to have a critical role in the pathogenesis of RA, this study aims to explore and reveal relevant ways by which TFP interacts with the chemical crosstalk between the gut microbiome and its host. 16S rRNA sequencing, combined with un-targeted metabolomics, were conducted on collagen-induced arthritis (CIA) rats. CIA model rats treated with TFP showed significant improvement in weight gain, pathological phenomena in joints, as well as decreased serum levels of TNF-α, IL-6 and increased level of IL-4 and IL-10. Significant dysfunction in the gut microbiome and alteration in serum metabolites were observed in CIA model rats, which were restored by TFP treatment. Coherence analysis indicated that TFP modulated the pathways of histidine metabolism, phenylalanine metabolism, alanine, aspartate, glutamate metabolism, amino sugar and nucleotide sugar metabolism owing to the abundances of Lactobacillus, Bacteroides, Prevotellaceae_UCG-001 and Christensenellaceae_R-7_group in the gut microflora. The corresponding metabolites involved L-histidine, histamine, phenylethylamine, asparagine, L-aspartic acid, D-fructose 1-phosphate, D-Mannose 6-phosphate, D-Glucose 6-phosphate, and Glucose 1-phosphate. In conclusion, this study reveals the ameliorative effects of TFP on RA through the chemical crosstalk that exists between the gut microbiota and its host, and also further enriches our understandings of the pathogenesis of RA.